Human amniotic fluid-based exposure levels of phthalates and bisphenol A mixture reduce INSL3/RXFP2 signaling. (May 2020) - Suteau, Valentine; Briet, Claire; Lebeault, Maÿlis; Gourdin, Louis; Henrion, Daniel; Rodien, Patrice; Munier, Mathilde
Highlights: Investigated INSL2/RXFP2 signaling using in vitro models. DEHP, DBP and bisphenol A mixture based upon human amniotic fluid level. DEHP, DBP and bisphenol A individually potentiate RXFP2 activity. DEHP, DBP and bisphenol A mixture reduces the response to INSL3. New mechanism of action for potential endocrine disrupting chemicals. Abstract: Background: The presence of chemical pollutants in the environment can affect human health. Epidemiological and in vivo experimental studies reveal reprotoxic effects (undescended testis) of phthalates (diethylhexyl phthalate (DEHP), dibutyl phthalate (DBP)) and bisphenol A (BPA), resulting in particular of a decrease in INSL3 ( Insulin-Like 3 peptide ) production. This hormone is essential for normal testis development and acts on a G protein-coupled receptor: RXFP2. Objectives: The aim of this study was to evaluate the individual and combined impacts of DEHP, DBP, and BPA on human RXFP2 (hRXFP2) activity. Methods: We used HEK293 cells transiently transfected with hRXFP2 and receptor activity was analyzed by measuring intracellular cAMP production. The mixture was established at concentrations reported in human amniotic fluid, for the three compounds. Results: Individually, DEHP, DBP and BPA increased the response to INSL3 by 19.3 to 27.5%. This potentiating effect was specific for RXFP2, because it was absent in the cells which did not express this receptor. On the other hand, and interestingly, the mixture of the three compounds reduced significantly the response to INSL3 by 12%, and the observed effects were opposite to those predicted, suggesting an antagonist effect. Discussion-Conclusion: Taken together, our results demonstrate for the first time that a mixture of phthalates and BPA present in human amniotic fluid disturbs the human RXFP2 function. Moreover, we demonstrate that mixture can produce potential antagonistic effects that are not displayed by the compounds, individually.